Analysis of Pu-Mu Interaction Diagram of C-Shaped Equal Legged RC Column Developed using ETABS and Analytical Method - Shet, Suraj; Shetty, Sabyath; Shetty, Shanmukha (International Journal of Engineering and Technology, 2018)
Interaction curve is a visual representation of bending moment (Mu) and axial force (Pu) and this curve explains the ultimate capacity of the compression member when it is subjected to axial load and moments. Interaction diagram for rectangular and circular columns are available in SP 16-1980 RC Handbook. Limit State Method of design approach is adopted for the analysis of the work. This work includes developing the interaction curve for C-shaped equal legged RC column with different grade of steel and concrete. Comparison of the interaction curve of the C-shaped equal legged RC column by using Analytical method with that of the ETABS is done, and their significance in civil fields.Â Â